(untitled) (Research, Society and Development, 2021)
This article presents a theoretical discussion that seeks to contribute to the following question: what should be done so that active methodologies are not just a fad? The research has a qualitative approach with a bibliographic study design. The research corpus first considered the concept of active methodologies according to several authors. In response to the central theme of the research, we defend the idea that sharing experiences about the use of active methodologies, at all levels of education, in all kinds of spaces and with the most varied resources, including teacher training courses that make use of these methodologies and developed activities that are theoretically grounded, are ways that can make the methodologies produce significant and lasting effects in education. Only discussions about the epistemology of active methodologies or unconstructive criticism of their use will contribute little to education. We consider the idea that these methodologies are today the best option we have for the promotion of quality education.